A demand analysis of the Spanish canned tuna market. (December 2017) - García-del-Hoyo, Juan José; Jiménez-Toribio, Ramón; Guillotreau, Patrice
Abstract: The Spanish market for canned fish is one of the biggest in the world. It is still largely supplied by a robust national industry which has survived globalisation when all other European countries failed to preserve their two-century old industry. What is so special about this relationship between Spanish consumers and canned fish? This research analyses the nature of the demand for canned fish, and particularly canned tuna, a rather inexpensive and storable food product, to show how Spanish households are sensitive to price and income changes. The price and expenditure elasticities are estimated through a time-based Almost Ideal Demand System (AIDS) model. A Johansen's multivariate time-series analysis was developed through a vector error correction model, the misspecification tests supporting the use of this model. The empirical analysis found that the Spanish demand for canned fish in Spain is rather price inelastic, whatever the species, but substitutability is found between the different canned fish products. The results also demonstrate that canned tuna over-reacts positively to expenditure changes compared to other fish species, presenting a nature of luxury good compared to other canned fish products.